COMPARATIVE STUDY OF THE SMALLER INTESTINE VILLUS EPITHELIUM UNDER EXPERIMENTAL PERITONITIS AND INTESTINAL OBSTRUCTION - Tamm, T.I.; Barduk, A.Y.; Govorucha, T.P.; Repin, N.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
A comparative study of the smaller intestine villus epithelium ultrastructure under experimental peritonitis and intestinal obstruction was carried-out. It was shown that ultrastructural rearrangements of the smaller intestine epithelium start after 6 hours of an inflammatory process. Destructive changes in cells under intestinal obstruction were more pronounced than under peritonitis.